SINIFICATION OF MARXISM IN CHINA AND HUMANIZATION OF MARXISM IN POLAND: A PHILOSOPHICAL CASE STUDY IN CONTEXT OF MODERNIZATION - Hu, Yeping (My University, 2011)
Badanie to przeprowadza analizy filozoficznej teorii i praktyki marksizmu w dwóch poszczególnych krajach rolniczych: Polska w Europie i Chinach w Azji. Bada ona takie pytania jak: dlaczego marksizmu została zaakceptowana przez te dwa kraje rolnej; jak dwa kraje interpretowane, zrozumiała, wdrożona i stosowana marksizmu; jak marksizm jako naczelną zasadą ideologicznych skorzystała z przysługującego jej roli w dwóch krajach w historii nowożytnej i współczesnej, jak przyjęli oni marksizm w zgodzie z ich własnych tradycji kulturowych transformacji ich mentalności i świadomości, jakie były ich wkład i krytyki marksistowskiej ortodoksji, jakie były konsekwencje i skutki ideologii marksistowskiej w ich konstrukcji społeczno-politycznych i gospodarczych; jak dwa kraje zareagowały na pojawiające się wyzwania społeczno-politycznych i gospodarczych, jakie są podobieństwa i różnice, a jakie wnioski należy wyciągnąć z ich doświadczeń historycznych odpowiednio. W celu szczególnym uwzględnieniem tych badań próbuje wybrać kilka postaci jako głównych przedstawicieli Polska i Chiny, jak każdy z tych liczb odegrała znaczącą i niezwykłą rolę w dostarczaniu teoretyczne lub praktyczne przywództwo w ruchu socjalistycznym i / lub istotne krytyki marksizmu. Badanie to będzie również ograniczyć się do niektórych aspektów marksistowskiego socjalizmu teorie, które są istotne zarówno Polska jak i Chiny. Podstawowa struktura pracy jest trzykrotnie, część I w Chinach, część II i część III Polska za wniosek.

This study conducts a philosophical analysis of the theory and praxis of Marxism in two particular agricultural countries: Poland in Europe and China in Asia. It explores such questions as why Marxism was accepted by these two agricultural countries; how the two countries interpreted, understood, implemented and applied Marxism; how Marxism as a guiding ideological principle exercised its role in the two countries during their modern and contemporary history; how they adopted Marxism in accord with their own cultural traditions for the transformation of their mentality and consciousness; what were their contributions to and critiques of Marxist orthodoxy; what were the consequences or effects of Marxist ideology in their socio-political and economic constructs; how the two countries responded to the emerging socio-political and economic challenges; what are the similarities and differences; and what lessons should be drawn from their historical experiences respectively. In order to have a specific focus this study attempts to select a few figures as major representatives from Poland and China as each of these figures has played a significant and remarkable role in providing theoretical or practical leadership in the socialist movement and/or crucial critiques of Marxism. This study will also limit itself to certain aspects of Marxist socialist theories which are relevant to both Poland and China. The basic structure of the study is threefold, Part I on China, Part II on Poland and Part III as conclusion.
Wydział Nauk Społecznych: Instytut Filozofii
Keywords: Sinification i Humanizacja marksizmu; Sinification and Humanization of Marxism; Chiny; China; Poland; Poland